PROTOTYPE SECURITY ALARM SYSTEM PADA KENDARAAN MOTOR - Elisa, Elisa; Alpianita, Pinni; Syam, Nurwahid; Farida, Farida (CV. LAJAGOE PUSTAKA, 2024)
The aims of this research are: (1) to make a tool that can be assembled on a Yamaha motorbike. (2) can be controlled via a smartphone which has a function as a safety on motorcycles using Arduino and the Security Alarm System. The research method used in this research is the prototyping method, which is a system manufacturing process method that is made in a structured manner and has several stages that must be passed in its manufacture, but if the final stage states that the system that has been made is not perfect or still has deficiencies, then the system will be re-evaluated and will go through the process from the beginning. Where this method has 6 stages, namely needs analysis, rapid design, build prototypes, initial user evaluation, improve prototypes, implementation and maintenance. The results of this study are: (1) Designing a prototype security alarm system on Arduino-based Yamaha motorcycles to implement a motorcycle security system that is reliable and responsive when the vehicle is parked. This system uses a vibration sensor to detect every movement and vibration that occurs in the vehicle, this system uses an alarm that can sound when the vehicle vibrates or moves and can make calls via smartphone. (2) Implementation of a security alarm system prototype on Arduino-based Yamaha motorbikes can be used to secure motorcycles from theft and vandalism.